Java extreme programming cookbook - Burke, Eric M. (O'Reilly, 2003)
Extreme Programming does not mean programming naked while rollerblading down the side of the Grand Canyon. It does mean a new approach to software development that is both radical and common-sense. Unlike many software development methodologies, XP has been accepted quickly because its core practices--particularly code sharing, test-first development, and continuous integration--resonated immediately with software developers everywhere. Instead of impressing developers with a body of theory, XP got programmers to say, "Yeah, that's how I'd like to work." Oddly enough, although most developers turn to Extreme Programming methods in order to code real, hands-on, and extensible projects quickly ("Code comes first"), most books on Extreme Programming insist on focusing on the theory and not the practice. Not the Java Extreme Programming Cookbook . Brimming with over 100 "recipes" for getting down to business and actually doing XP, the Java Extreme Programming Cookbook doesn't try to "sell" you on XP; it succinctly documents the most important features of popular open source tools for XP in Java--including Ant, Junit, HttpUnit, Cactus, Tomcat, XDoclet--and then digs right in, providing recipes for implementing the tools in real-world environments. Each recipe offers solutions that help you put an extreme programming environment together: then provides code for automating the build process and testing. Although the time saved using any one of these solutions will more than pay for the book, Java Extreme Programming Cookbook offers more than just a collection of cut-and-paste code. Each recipe also includes explanations of how and why the approach works, so you can adapt the techniques to similar situations. One of the biggest challenges facing developers today is sorting through the wide variety of tools available form various source and figuring out how to them effectively. The recipes in Java Extreme Programming Cookbook showcase how to use the most important features of these XP tools. Many of these tools are geared towards unit testing, while others are invaluable for continuous integration; with these practical examples, you'll be able to choose the most effective tools to accomplish your goals, then implement them in a cohesive development environment quickly. If you want to set up a test-driven development environment that allows you to focus on writing testable code--now--this book will prove invaluable